College writing skills with readings - Langan, John. ([Place of publication not identifed] : McGraw Hill Education, 2011)
This book offers students a practical guide to becoming better writers. It comes with innovative connect writing software, providing additional guided practice for college writers.
Part1. Essay writing -- Part2. Patterns of essay development -- Part3. Special skills -- Part4. Handbook of sentence skills -- Part5. Readings for writers .
Includes index.
Keywords: ENGLISH LANGUAGE--RHETORIC